A facile one-pot synthesis of Co2P nanoparticle-encapsulated doped carbon nanotubes as bifunctional electrocatalysts for high-performance rechargeable Zn–air batteries. Issue 4 (5th January 2021) - Shao, Qi; Li, Tianjiao; Wang, Heng-guo; Li, Yanhui; Si, Zhenjun; Duan, Qian
Abstract : One-pot synthesis of Co2 P nanoparticles encapsulated into doped carbon nanotubes, which can be applied as ORR/OER bifunctional catalysts for Zn–air batteries. Abstract : The reasonable design of inexpensive, active and robust electrocatalysts for the oxygen evolution reaction (OER) and the oxygen reduction reaction (ORR) is crucial but challenging in the renewable energy area. Herein, a facile design is developed for one-pot fabrication of Co2 P nanoparticles encapsulated into doped carbon nanotubes (Co2 P@NPCNTs) by a self-catalyzed growth strategy. Notably, this methodology can avoid not only the use of organic solvents and toxic alkyl phosphines, but also the requirement of complicated operations, sophisticated instruments and costly precursors. More importantly, the unique encapsulation structure between the NPCNTs and Co2 P nanoparticles can endow the hybrids with fast electronic transport and favorable stability for both the ORR and OER. The obtained catalysts show low Tafel slopes (49.8 mV dec −1 for the ORR and 62.4 mV dec −1 for the OER) and considerable bifunctional catalytic performance. Impressively, as the air-cathode catalysts for zinc–air batteries, the Co2 P@NPCNTs also show excellent open-circuit voltage, good charge–discharge performance and stability. Overall, an efficient and scalable method together with good catalytic performance endows the Co2 P@NPCNT catalysts with enormous potential for large-scale electrochemical energy applications.